Adult playfulness: An update on an understudied individual differences variable and its role in romantic life. Issue 4 (16th March 2021) - Brauer, Kay; Proyer, René T.; Chick, Garry
Abstract: There is increasing interest in the study of individual differences in playfulness in adults; the way people frame or reframe situations in a way that they are experienced as personally interesting, and/or intellectually stimulating, and/or entertaining. In this review, we describe and discuss its role for romantic life. After a brief introduction, we will describe theoretical approaches as to why playfulness is important in romantic life (e.g., the signal theory of playfulness) and give an overview on empirical findings on assortative mating and its role in romantic relationships (e.g., for relationship satisfaction). Finally, we discuss future directions on playfulness in romantic life and singles and open research questions.